2015
DOI: 10.1088/1748-9326/10/9/095010
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the environmental justice consequences of flood risk: a case study in Miami, Florida

Abstract: Recent environmental justice (EJ) research has emphasized the need to analyze social inequities in the distribution of natural hazards such as hurricanes and floods, and examine intra-ethnic diversity in patterns of EJ. This study contributes to the emerging EJ scholarship on exposure to flooding and ethnic heterogeneity by analyzing the racial/ethnic and socioeconomic characteristics of the population residing within coastal and inland flood risk zones in the Miami Metropolitan Statistical Area (MSA), Florida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 29 publications
4
49
0
1
Order By: Relevance
“…This positive association between rating the proximity to a river or lake as a more important consideration when selecting the current home and greater odds of flood risk is expected based on the literature [25,47,48,49]. …”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…This positive association between rating the proximity to a river or lake as a more important consideration when selecting the current home and greater odds of flood risk is expected based on the literature [25,47,48,49]. …”
Section: Discussionmentioning
confidence: 74%
“…Despite flood hazards being framed as an environmental injustice issue by only a small body of literature [21], studies on race/ethnicity and flood exposure have found that minorities may be disproportionately exposed in some contexts [12,22,23,24,25,26], and that the heightened exposure of minorities to hazards often has historically unjust roots. In Austin (TX, USA), periodic flooding was a factor in the racial segregation of the city, where Hispanics and Blacks were marginalized to areas most prone to flooding [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve a fair distribution, the political discussion and especially institutions (formal and informal) have to be changed. Justice in natural hazard and risk management demands more than just a fair socio-economic distribution or recognition of cultural roots (Campbell 2012;May and Morrow 2012;Neal et al 2014;Zwarteveen and Boelens 2014). Justice also relates to the process by which a certain distribution is selected (procedural justice), but this aspect is not covered by this paper.…”
Section: Social Justices In Natural Hazard Managementmentioning
confidence: 99%
“…Floods account for 43% of all natural disasters [1] that cause death, adverse health effects, property damage, and socio-economic imbalance [2][3][4]. By 2001, flooding became seven times more frequent around the world compared to 1975.…”
Section: Introductionmentioning
confidence: 99%